Design of sub-THz traveling wave tubes for high data rate long range wireless links. (30th October 2018) - Basu, Rupa; Billa, Laxma R; Letizia, Rosa; Paoloni, Claudio
Abstract: The development of high capacity wireless networks, to satisfy the increasing demand of mobile high-speed internet, is stimulating the exploitation of the wide frequency bands in the millimeter and THz range. Above 100 GHz, the high atmosphere attenuation is the major obstacle for wireless links of adequate length, due to the low power available from solid state amplifiers. Traveling wave tubes (TWT) are promising devices capable og generating multi-watt power at sub-THz frequency. In this paper, the design and performance of a TWT in the 210–250 GHz band with about 1 W output power will be described, to power a 40 Gigabits per second optical transmitter for 1 km point-to-point link. A novel approach for a simple and low-cost fabrication, based on the use of the double corrugated waveguide is proposed.